2022
DOI: 10.3390/foods11182851
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perspectives of the Impact of COVID-19 Lockdown on Food-Related Behaviors: Systematic Review

Abstract: Home confinement during the COVID-19 pandemic has been accompanied by dramatic changes in household food dynamics that can significantly influence health. This systematic literature review presents parental perspectives of the impact of COVID-19 lockdown (up to 30 June 2022) on food preparation and meal routines, as well as other food-related behaviors, capturing both favorable and unfavorable changes in the household food environment. Themes and trends are identified and associations with other lifestyle fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 144 publications
2
6
0
Order By: Relevance
“…Our research shows that most respondents shop for groceries online in order to save time, have a wider choice of products and due to more convenient and easier searching. This statement is consistent with the views of many authors (e.g., [ 49 , 50 , 51 ]) and such progress can be expected in the future [ 73 ], because digitalization plays a crucial role [ 74 ]. Even some studies found that virtual reality technology is effective for online shopping [ 75 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our research shows that most respondents shop for groceries online in order to save time, have a wider choice of products and due to more convenient and easier searching. This statement is consistent with the views of many authors (e.g., [ 49 , 50 , 51 ]) and such progress can be expected in the future [ 73 ], because digitalization plays a crucial role [ 74 ]. Even some studies found that virtual reality technology is effective for online shopping [ 75 ].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, however, these virtuous changes were combined with overeating and increased snacking on high-calorie snacks, desserts, and sweets. Moreover, food insecurity increased among the lowest-income families [20]. Altogether, all these elements are in agreement with the increased incidence of overweight, obesity and type 2 diabetes mellitus detected during the lockdown confinement [21].…”
Section: Discussionsupporting
confidence: 79%
“…Policymakers should consider the potential health consequences of future prolonged pediatric age individuals' confinement, including their exposure to sunlight and opportunities for outdoor activities. Obesity prevention and treatment initiatives, as well as ongoing efforts to address nutritional management, parental feeding practices, and food insecurity, may account for these changes in the future [20]. Moreover, since optimal serum levels of vitamin D for bone and general health may not be the same and are also likely to fluctuate with life stages, race, ethnicity, and the specific measures used for assessing a wide variety of physiological processes, further studies appear necessary to determine which are the optimal indications for vitamin D supplementation [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of food at home, combined with boredom and emotional triggers, can increase the likelihood of consuming high-calorie, low-nutrient foods. Limited access to fresh and nutritious meals and reliance on processed and convenience foods can further exacerbate unhealthy eating habits during periods of crisis [ 35 , 36 , 37 ].…”
Section: Psychological Impact Of Pandemics On Childhood Obesitymentioning
confidence: 99%